2014
DOI: 10.1128/aac.01099-13
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Dissemination of CTX-M-15 Genotype Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae among Patients Presenting to Community Hospitals in the Southeastern United States

Abstract: e Extended-spectrum-␤-lactamase (ESBL)-producing organisms are increasingly prevalent. We determined the characteristics of 66 consecutive ESBL-producing isolates from six community hospitals in North Carolina and Virginia from 2010 to 2012. Fiftythree (80%) ESBL-producing isolates contained CTX-M enzymes; CTX-M-15 was found in 68% of Escherichia coli and 73% of Klebsiella isolates. Sequence type 131 (ST131) was the commonest type of E. coli, accounting for 48% of CTX-M-15-producing and 66% of CTX-M-14-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 18 publications
4
40
1
2
Order By: Relevance
“…Our results showed that 96.5 % of the ESBL-E. coli isolates encoded genes of the CTX-M group with or without TEM-encoding genes, suggesting the emergence of the CTX-M gene group as the main contributor to the antibiotic resistance of ESBL-E. coli in food, foodproducing animals, healthy people, and patients not only in developed countries but also in underdeveloped countries (Sasaki et al 2010;Overdevest et al 2011;Börjesson et al 2013;Chen et al 2014;Nakayama et al 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results showed that 96.5 % of the ESBL-E. coli isolates encoded genes of the CTX-M group with or without TEM-encoding genes, suggesting the emergence of the CTX-M gene group as the main contributor to the antibiotic resistance of ESBL-E. coli in food, foodproducing animals, healthy people, and patients not only in developed countries but also in underdeveloped countries (Sasaki et al 2010;Overdevest et al 2011;Börjesson et al 2013;Chen et al 2014;Nakayama et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The phylogenetic groups of ESBL-E. coli were identified by multiplex PCR amplification of a combination of two genes, chuA and yjaA, and a DNA fragment, TspE4C2, as described previously (Chen et al 2014). …”
Section: Determination Of Phylogenetic Groupsmentioning
confidence: 99%
“…It has been reported that the ESBL prevalence is higher in Europe than in the USA but lower in Asia or South America (4). Sequence type (ST) 131 is the most common genotype of ES-BL-producing E. coli, and 54.2% of community-associated infections are caused by the ST131 strain (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ESBL-producing bacteria typically carry genetic determinants that confer resistance to fluoroquinolones and aminoglycosides. Thus, carbapenems, along with other drugs, such as Beta-lactam/beta-lactamase inhibitor combinations, may likely have an increasing role as empirical therapy for patients who are infected with ESBL-producing organisms in community and hospitals (15). In summary, we found an ESBL-producing E. coli in a 1-month-old infant with a blood cancer that carried CTX-M-1 group enzymes.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, in cancer patients with prolonged hospitalization and with ALL who had received antibiotics for a prolonged period, the opportunity for these bacteria to cause infections enhances (14). Recent data have documented the importance of CTX-M enzymes in the ESBL epidemic around the world (15). ESBLproducing organisms, especially those carrying CTX-M-15, are commonly resistant to cephalosporins as the first-line choice for the treatment of bacteremic patients.…”
Section: Discussionmentioning
confidence: 99%